Exploring food and healthy eating with newcomers in Winnipeg's North End. Issue 1 (6th March 2017) - Henderson, Amy; Epp-Koop, Stefan; Slater, Joyce
Abstract : Purpose: The purpose of this paper is to explore the challenges and opportunities associated with attempting to maintain a healthy traditional diet for newcomers living in the North End neighbourhood of Winnipeg, Canada. Design/methodology/approach: In this mixed-methods photovoice study the researcher used food photographs taken by participants to facilitate in-depth, semi-structured interviews with newcomers living in the area of interest. Community workers involved in food and newcomer programming were also interviewed. Qualitative data from the interviews were analysed using thematic analysis. Food security status of newcomer participants was also determined using The Household Food Security Survey Module. Findings: Newcomer participants reported many struggles, including low incomes, gardening challenges and little access to culturally acceptable foods. Community worker interviews, field notes and an environmental scan of community resources also revealed a lack of social inclusion/support and few food and nutrition resources for newcomers. Originality/value: Newcomers to Canada experience high rates of food insecurity and diminishing health status associated with length of time in Canada. This study demonstrates an imminent need for additional resources and programmes in this inner city community in order to decrease food security rates and help newcomers in Winnipeg to eat healthy traditional diets and avoid a decline in health.